2017
DOI: 10.1111/opo.12354
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral aberrations in adult hyperopes, emmetropes and myopes

Abstract: Hyperopes and emmetropes had greater relative peripheral myopia than myopes. There was asymmetry in RPRE along the vertical meridian for hyperopes which was not present in the emmetropes, suggesting there may be asymmetries in peripheral eye length along the vertical meridian for the former. Higher-order aberrations were affected by field eccentricity, but refractive error affected only the spherical aberration coefficient, which was more positive for hyperopes than for other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…Population weighted average Zernike co‐efficients for the horizontal VF are listed in Table . The values were obtained using all studies from Table with available wavefront data . Calculations for each angular position were made for a 4 mm pupil diameter using the full extent of available wavefront data, that is all Zernike co‐efficients and all angles reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population weighted average Zernike co‐efficients for the horizontal VF are listed in Table . The values were obtained using all studies from Table with available wavefront data . Calculations for each angular position were made for a 4 mm pupil diameter using the full extent of available wavefront data, that is all Zernike co‐efficients and all angles reported.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral ocular aberrations and their effect on retinal image quality were assessed using data from 16 articles, listed in Table . For three studies, marked with an asterisk, wavefront data for each individual subject were generously shared by the authors .…”
Section: Peripheral Ocular Aberrations Datamentioning
confidence: 99%
“…Off‐axis HOAs are typically of greater magnitude than on‐axis HOAs, particularly for coma terms, likely as a result of the change in alignment and shape differences of the ocular refractive surfaces from off‐axis incident light rays . Changes in off‐axis HOAs also occur with age.…”
Section: Hoas and Agementioning
confidence: 93%
“…Cross‐sectional studies of off‐axis HOAs in young adults have shown that HOA RMS increases more rapidly with visual field eccentricity in myopes than in emmetropes; however, Osuagwu et al found no significant differences between refractive error groups. Consistent with the findings of on‐axis HOA studies, myopes exhibit more negative primary spherical aberration (Z40) than emmetropes, and hyperopes display more positive primary spherical aberration (Z40) than emmetropes and myopes on average across the visual field .…”
Section: Hoas and Refractive Errormentioning
confidence: 97%
See 1 more Smart Citation